Platelet-Derived Chemokine CXCL7 Dimer Preferentially Exists in the Glycosaminoglycan-Bound Form: Implications for Neutrophil–Platelet Crosstalk - Brown, Aaron J.; Sepuru, Krishna Mohan; Sawant, Kirti V.; Rajarathnam, Krishna (Frontiers in Immunology, 2017)
Platelet-derived chemokine CXCL7 (also known as NAP-2) plays a crucial role in orchestrating neutrophil recruitment in response to vascular injury. CXCL7 exerts its function by activating the CXCR2 receptor and binding sulfated glycosaminoglycans (GAG) that regulate receptor activity. CXCL7 exists as monomers, dimers, and tetramers, and previous studies have shown that the monomer dominates at lower and the tetramer at higher concentrations. These observations then raise the question: what, if any, is the role of the dimer? In this study, we make a compelling observation that the dimer is actually the favored form in the GAG-bound state. Further, we successfully characterized the structural basis of dimer binding to GAG heparin using solution NMR spectroscopy. The chemical shift assignments were obtained by exploiting heparin binding-induced NMR spectral changes in the WT monomer and dimer and also using a disulfide-linked obligate dimer. We observe that the receptor interactions of the dimer are similar to the monomer and that heparin-bound dimer is occluded from receptor interactions. Cellular assays also show that the heparin-bound CXCL7 is impaired for CXCR2 activity. We conclude that the dimer-GAG interactions play an important role in neutrophil-platelet crosstalk, and that these interactions regulate gradient formation and the availability of the free monomer for CXCR2 activation and intrathrombus neutrophil migration to injury site.